Kontribusi Waqf Gontor Terhadap Kesejahteraan Masyarakat Desa Gontor - Adib Susilo (Islamic Economics Journal, 2016)
Waqf is one of Islamic Filantrophy heritage, there is lot of institutions capable of fostering community with waqf and even in the history, waqf capable to building civilization. Gontor the first cottage standing and becomes waqf, so they no longer belong to the family or private. But unfortunately the nearby village community of Gontor that should feeling the impact of Gontor welfare can not so visible. Which Visible is the welfare gaps between Gontor and Society.This research is a qualitative research with Gontor villagers as the object who have direct or indirect relationship with Gontor as well as people who are not related to Gontor but stayed in the Gontor village. the method used is non-prbability sampling that is purposive sampling. Data collected through interviews, and documentation. Data were analyzed by using the method of Miles and Huberman through data reduction, data display and then summed to determine the contribution of Gontor waqf Against Neighborhood soceity. The results of this study is that the management of Waqf in Gontor runs very well even with the emergence of a rapidly growing business units, Gontor productive waqf also seek to contribute to the welfare of the village community Gontor, and all indicators of Maqasid Shari’ah can be met, especially in the field of economic independence.